Corticotomy as one of methods to accelerate duration of orthodontic treatment: Corticotomy sebagai salah satu metode untuk mempercepat durasi perawatan ortodonti - Hillery Getroida Torar; Susilowati (Makassar Dental Journal, 2023)
Malocclusion is a dental disorder that ranks third after dental caries and periodontal disease in dental and oral health problems in Indonesia. Early detection will facilitate orthodontic treatment and prevent the malocclusion from getting worse which can result in the need for more complex orthodontic treatment. Most conventional orthodontic treatments take more than a year to com-plete. Orthodontic facilitated corticotomy is a therapeutic procedure that assists orthodontic tooth movement by accelerating bone metabolism due to controlled surgical damage. The objective of this review is to find out that corticotomy can be used as a one of the methods an accelerating duration orthodontic treatment, so it is made through a literature search using a search en-gine from several sources related to the topic to be discussed. Corticotomy is one of the methods in accelerating tooth move-ment through invasive surgical treatment. It is concluded that corticotomy facilitated orthodontic tooth movement showed 1.5-2 times faster than with conventional orthodontic. However, corticotomy has disadvantages such as additional cost for perio-dontal surgery and less pain on the first day after surgery. .